Mechanical properties of organic matter in shales mapped at the nanometer scale. (January 2015) - Eliyahu, Moshe; Emmanuel, Simon; Day-Stirrat, Ruarri J.; Macaulay, Calum I.
Abstract: The mechanical properties of organic matter strongly affect the way shales deform and fracture. However, the way organic matter responds to mechanical stresses is poorly understood, representing a critical obstacle to assessing oil and gas production in shale formations. Little is known about the mechanical properties of organic matter in fine grained rocks primarily because it often occupies tiny nanometer-scale voids between the mineral grains which cannot be accessed using standard mechanical testing techniques. Here, we use a new atomic force microscopy technique (PeakForce QNM™) to map the mechanical properties of organic and inorganic components at the nanometer scale. We find that the method is able to distinguish between different phases such as pyrite, quartz, clays, and organic matter. Moreover, within the organic component Young's modulus values ranged from 0 to 25 GPa; in 3 different samples – all of which come from thermally mature Type II/III source rocks in the dry gas window – a modal value of 15–16 GPa was measured, with additional peaks measured at ≤10 GPa. In addition, the maps suggest that some porous organic macerals possess a soft core surrounded by a harder outer shell 50–100 nm thick. Thus, our results demonstrate that the method represents a powerful new petrographic tool with which to characterize the mechanical properties of organic-rich sedimentary rocks. Highlights: New atomic force microscope method (PeakForce QNM™) is used to measure moduli in shales. The technique yields modulus maps with nanometer resolution. Young's modulus of organic matter is highly variable with values in the range 0–25 GPa. Nano-scale mechanical structure of macerals shows that some may have a hard shell and soft core.